2021
DOI: 10.3390/ijms22189732
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact and Functional Annotations of KIF11 and KIF14 Expression in Patients with Colorectal Cancer

Abstract: Genomic instability (GIN) has an important contribution to the pathology of colorectal cancer (CRC). Therefore, we selected mitosis and cytokinesis kinesins, KIF11 and KIF14, as factors of potential clinical and functional value in CRC, as their aberrant expression has been suspected to underlie GIN. We examined the expression and the prognostic and biological significance of KIF11 and KIF14 in CRC via in-house immunohistochemistry on tissue microarrays, public mRNA expression datasets, as well as bioinformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…MKI67, a marker gene in the cell cycle, also has been reported with prognostic value in NSCLC (62) and breast cancer (63). Furthermore, the prognostic value of KIF11 has been reported in oral cancer (64) and colorectal cancer (65).…”
Section: Discussionmentioning
confidence: 94%
“…MKI67, a marker gene in the cell cycle, also has been reported with prognostic value in NSCLC (62) and breast cancer (63). Furthermore, the prognostic value of KIF11 has been reported in oral cancer (64) and colorectal cancer (65).…”
Section: Discussionmentioning
confidence: 94%
“…As a crucial member of the kinesin family, KIF14 has been reported to be a regulator of tumor development and progression in previous studies and could also be a potential biomarker in the management of patients with cancer ( 24 , 25 ). A prior study revealed that KIF14 inhibition using small interfering (si)RNA could repress proliferation and enhance apoptosis in medulloblastoma cells, while KIF14 inhibition using short hairpin RNA could suppress cell viability, colony formation, invasion, migration and tumor sphere formation in medulloblastoma cells ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, KIF14 was upregulated in tumor tissues and could predict unfavorable outcomes in patients with ovarian cancer ( 29 ). These aforementioned studies indicated that in numerous types of cancer, KIF14 might be a promoter of cancer progression, and could be a potential biomarker for prognosis ( 21 , 24 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Histologically normal tissues adjacent to the tumor were available for 27 cases, and these constituted the control group. The same cohort of patients was previously described [36]. This study was carried out in accordance with the guidelines of the Declaration of Helsinki.…”
Section: Patients and Tissue Materialsmentioning
confidence: 99%
“…Immunohistochemical (IHC) staining was performed on tissue microarrays, the construction of which was described in our previous reports [36,37]. SPDL1 protein was stained in BenchMark ® ULTRA (Roche Diagnostics/Ventana Medical Systems, Tucson, AZ, USA) using ultraView Universal DAB Detection Kit (Roche Diagnostics/Ventana, Tucson, AZ, USA) according to the previously validated protocol [7].…”
Section: Tissue Microarrays and Immunohistochemical Stainingmentioning
confidence: 99%